2014
DOI: 10.1007/s10142-014-0423-y
|View full text |Cite
|
Sign up to set email alerts
|

The AKR gene family and modifying sex ratios in palms through abiotic stress responsiveness

Abstract: Sex ratio (SR), the ratio of female inflorescences to total inflorescences, is one of the main yield components of oil palm (Elaeis guineensis Jacq). The SR quantitative trait locus (QTL) was recently identified on linkage (LG) 8 with a phenotype variance explained (PVE) of 11.3 %. The use of both genetic and physical mapping is one strategy for uncovering the genetic basis of the traits. Here, we report the construction of bacterial artificial chromosome (BAC) and fosmid libraries, and their use for physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Indeed, Somyong et al (2014Somyong et al ( , 2015 described a putative aldo-keto reductase gene (named EgAKR1) which was revealed as a promising candidate for sex ratio determination via the control of female inflorescence number. More recently, Somyong et al (2016) Fig.…”
Section: Climate Change and Sex Ratiomentioning
confidence: 99%
“…Indeed, Somyong et al (2014Somyong et al ( , 2015 described a putative aldo-keto reductase gene (named EgAKR1) which was revealed as a promising candidate for sex ratio determination via the control of female inflorescence number. More recently, Somyong et al (2016) Fig.…”
Section: Climate Change and Sex Ratiomentioning
confidence: 99%
“…On the basis of expression characteristics, Solyc09g011240.3.1 , Solyc07g043570.3.1 , and Solyc01g106450.3.1 were silenced in tomatoes by the VIGS system, which showed sensitivity to drought and salt stresses with low contents of Pro and POD and high content of MDA at each stress stage ( Figure 10 ). The overexpression of OsAKR4C15 in A. thaliana lines resulted in lower contents of MDA and MG under both stresses and control conditions than wild types [ 32 ]. These results suggested that AKR members of tomatoes were in response to drought and salt stresses and that Solyc09g011240.3.1 , Solyc07g043570.3.1 , and Solyc01g106450.3.1 might play positive roles in regulating the tolerance of tomatoes in drought and salt stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, it will be of great interest to compare data between different palm species with contrasting sexual systems, including species such as oil palm which display environmentally regulated sex determination (Adam et al ., ). In this context, the recently published oil palm genome (Singh et al ., , b) is an invaluable resource and has already been used to identify a genomic region of importance to sex regulation (Somyong et al ., ). The region in question contains a putative aldo‐keto reductase gene that might be involved in abiotic stress response.…”
Section: Genetic and Molecular Basis Of Sexual Separationmentioning
confidence: 97%